Historic foraging ecology of the endangered Lahille's bottlenose dolphin (Tursiops truncatus gephyreus) inferred by stable isotopes - Campos Rangel, Andrea; Bastida, Ricardo Oscar; Fruet, Pedro; Laporta, Paula; Cappozzo, Humberto Luis; Valdivia, Meica; Vermeulen, Els; Botta, Silvina (Estuarine, Coastal and Shelf Science)
The main aim of this work was to evaluate historical changes in the foraging ecology of Lahille's bottlenose dolphin (Tursiops truncatus gephyreus) along its distributional range. Stable isotopes of carbon (δ13C) and nitrogen (δ15N) were analyzed in bone samples from specimens deposited in scientific institutions from Brazil (BR), Uruguay (UY) and Argentina (ARG), collected in periods PI (1903–1980) and PII (1981–2016). The isotopic values of ARG dolphins were different from UY and BR in both periods, reflecting variations in the composition of the diet and/or basal isotopic values. The considerably broad isotopic niche of the ARG dolphins was maintained in PII, following the trend of stable carbon and nitrogen isotopic values along the decades. In this area, mixing models showed a diet with a high proportion of demersal prey, mainly from coastal marine waters. Lahille's bottlenose dolphins from UY showed a stability in nitrogen isotopic values but increasing carbon isotope values through decades. This increasing trend was consistent with a lower use of the Río de la Plata estuarine waters by the species reported for the last decades. In these areas, the species also showed a high proportion of demersal fish species. Finally, ARG and UY dolphins showed a partial and a total isotopic niche segregation during Periods I and II, respectively, probably reflecting a spatial/ecological structuring in this region. BR and UY samples, on the other hand, were not statistically different, probably forming an ecological unit. The retrospective analysis of the Lahille's bottlenose dolphin diet contributed to the knowledge of the ecological structure and feeding behavior of this poorly-known subspecies. Fil: Campos Rangel, Andrea. Universidade Federal do Rio Grande; Brasil Fil: Bastida, Ricardo Oscar. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias ...